Advanced design of large cavern intersections in soft ground without conventional bar reinforcement. Issue 4 (4th August 2021) - Laubbichler, Jürgen; Schwind, Thomas; Gakis, Angelos; Sanz, Alejandro; Soto, Francisco
Abstract: The design of three mined stations in Toronto as part of the Eglinton Crosstown Light Rail Project involved several intersections of large tunnels situated in the heterogenous, water‐bearing glacial till deposits. The most challenging openings, 220 m 2 each, were formed in the two sides of the 18 m high cross‐cut tunnels to allow the excavation of the 18 m wide platform caverns. A key objective for the design was the optimization of the tunnel shapes and the advanced simulation of the fibre reinforced shotcrete properties, to allow these openings in the initial tunnel linings to be achieved without conventional bar reinforcement or thickenings, thus simplifying and accelerating the construction, whilst reducing health and safety risks. Advanced numerical analyses were utilized to simulate the staged excavation and support steps introducing advanced material models that accounted for the non‐linear behaviour of both soil and structural elements. The end product was an optimized design of the tunnel linings with synthetic fibre reinforced shotcrete without conventional reinforcement that was successfully implemented in the construction.